Profile of the paulista public school principal - Hojas, Viviani Fernanda [UNESP]; Abdian, Graziela Zambao [UNESP] (Univ Federal Santa Maria, 2015)
The aim of this paper was to analyze the possible profile (s) of the of the paulista public school principal, questioning the literature in the area, public service exams and policy guidelines, ambos from the state, in a historical perspective. The findings allowed us to state that, despite advances in the 1980s, mainly regarding the denial of business Administration and the incentive for the construction of a theoretical body proper to school Administration, what predominates in more recent years is the non-initial training of the school principal and a performance based on the manager. The achieved advances found real (and pragmatic) barriers when this examined principal is submitted to continued training courses and to legislation that determine a managerial profile, emptied of other possibilities for not dialoguing with an alternative strengthened initial training regarding what is received daily from higher courts.
Keywords: Public School Principal; Theoretical Production in School Administration; Paulista Educational Policy